Barrier protective effects of 2,4,6-trihydroxy-3-geranyl acetophenone on lipopolysaccharides-stimulated inflammatory responses in human umbilical vein endothelial cells - Yi, Joong Chong; Musa, Nazmi Firdaus; Ng, Chean Hui; Shaari, Khozirah; Israf, Daud Ahmad; Chau, Ling Tham (Elsevier, 2016)
Pharmocological relevance: 2,4,6-trihydroxy-3-geranyl acetophenone (tHGA), is a phloroglucinol compound found naturally in Melicope ptelefolia. Melicope ptelefolia has been used traditionally for centuries as natural remedy for wound infections and inflammatory diseases.